1997
DOI: 10.1152/ajpcell.1997.272.6.c1980
|View full text |Cite
|
Sign up to set email alerts
|

Confocal imaging analysis of ATP-induced Ca2+ response in individual endothelial cells of the artery in situ

Abstract: The mechanisms for mobilization of intracellular free Ca2+ have been studied in various types of isolated and cultured cells, but little is known about Ca2+ mobilization in individual cells in situ. We tried to establish imaging analysis of intracellular free Ca2+ concentration ([Ca2+]i) in individual cells loaded with the acetoxymethyl ester of fluo 3 in situ, using laser scanning confocal microscopy. The method permitted us to distinguish signals from endothelial and smooth muscle cells of guinea pig artery.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(16 citation statements)
references
References 18 publications
3
13
0
Order By: Relevance
“…ADP and ATP-mediated endothelium-dependent relaxations in guinea pig aorta were inhibited by the P2Y 1 receptor-selective antagonist MRS2179; UTP relaxations were insensitive to MRS2179 and UDP was inactive, suggesting an involvement of P2Y 4 receptors (Kaiser and Buxton, 2002). Ca 2+ waves within endothelial cells are induced by ATP, but not UTP, via P2Y receptors in guinea pig aortic strips (Ohata et al, 1997), consistent with a likely expression of P2Y 1 and P2Y 4 but not P2Y 2 receptors in this vessel. In mouse thoracic aorta, P2Y 1 , P2Y 2 , and P2Y 6 receptors are present on endothelial cells and mediate vasorelaxation (Bény, 2004;Guns et al, 2005).…”
Section: A Aortamentioning
confidence: 89%
See 1 more Smart Citation
“…ADP and ATP-mediated endothelium-dependent relaxations in guinea pig aorta were inhibited by the P2Y 1 receptor-selective antagonist MRS2179; UTP relaxations were insensitive to MRS2179 and UDP was inactive, suggesting an involvement of P2Y 4 receptors (Kaiser and Buxton, 2002). Ca 2+ waves within endothelial cells are induced by ATP, but not UTP, via P2Y receptors in guinea pig aortic strips (Ohata et al, 1997), consistent with a likely expression of P2Y 1 and P2Y 4 but not P2Y 2 receptors in this vessel. In mouse thoracic aorta, P2Y 1 , P2Y 2 , and P2Y 6 receptors are present on endothelial cells and mediate vasorelaxation (Bény, 2004;Guns et al, 2005).…”
Section: A Aortamentioning
confidence: 89%
“…It has been shown that Ca 2+ waves within endothelial cells are induced by ATP via P2Y (P2Y 1 ), but not P2U (P2Y 2 and/or P2Y 4 ), receptors in guinea pig aortic strips (Ohata et al, 1997). ATP stimulates L-arginine uptake and NO release from porcine aortic endothelial cells (Bogle et al, 1991).…”
Section: Purinergic Signaling and Blood Vesselsmentioning
confidence: 99%
“…Use of a confocal imaging system would allow us to discriminate between the endothelial cells and the smooth muscle cells, and, furthermore, the real-time imaging of the [Ca 2ϩ ] i dynamics in these cell layers along the z-axis would be possible if scanning were conducted using a piezoelectric actuator added to the real-time scanning system. In practice, Ohata et al 21 previously demonstrated the confocal images of [Ca 2ϩ ] i in endothelial cells in situ with clear discrimination from the smooth muscle layer.…”
mentioning
confidence: 99%
“…In practice, we have established an imaging analysis protocol with respect to [Ca 2+ ] i in individual endothelial cells in situ with LSCM (12,13). However, LSCM led to increased photodamage with total time necessary to acquire images, especially during continuous imaging.…”
Section: +mentioning
confidence: 99%